Позитронные и позитрониевые состояния в графитоподобном нитриде бора - Арефьев К. П. Константин Петрович; Суров Ю. П.; Боев О. В. Олег Владимирович; Лопатин В. В. Владимир Васильевич (1984, 1984)
В фонде НТБ ТПУ отсутствует